Identification of Maqasid al-Syari'ah Based Business Scale Up Patterns in the One Pesantren One Product (OPOP) Program in Ciamis Regency - Muhammad Zaki Rahman; Cici Cahyati; Siti Robiyatul; Hanum Salsa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In Ciamis Regency, there are several Islamic boarding schools that participate in the One Pesantren One Product (OPOP) program under the guidance of the West Java Provincial Government which is promoted starting in 2019 which aims to raise various products spread across various Islamic boarding schools. Some pesantren have business products that have been running on a scale-up basis. Because the business that is run is in the Islamic boarding school environment, the business applied uses the concept of sharia economics. Product buying and selling transactions (muamalah) are not only aimed at obtaining profitability or profit, but are in line with morals, ethics and the objectives of the Shari'a. The method used in this study is a descriptive method with a qualitative approach. The holding of the One Pesantren One Product (OPOP) program is expected that Islamic boarding school managers or communities in the pesantren environment can improve the economy of the local community by following the concept according to the rules of shari'ah. This program is one of the programs of the West Java Provincial Government that focuses and is committed to the development of pesantren product commerce, with the concept of